2021
DOI: 10.1039/d1ra05667k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydrofluorination reaction on structure and properties of PVDF electrospun fibers

Abstract: A piezoelectric nanosensor was prepared with a novel type of dehydrofluorinated poly(vinylidene fluoride) (PVDF) nanofibrous membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Second, when matching with the Li metal anode, the alkaline radicals on the surface of Li metal rapidly induce the uncontrolled dehydrofluorination of PVDF‐HFP (–(CH 2 –CF 2 )‐ + LiOH → –(CHCF)‐ + LiF + H 2 O), resulting in the formation of unstable solid electrolyte interphase (SEI) with porous structure. [ 33,34 ] The porous structure of the SEI layer leads to continuous side reactions between Li metal and solvated molecules, resulting in the further deterioration of interfacial stability. In addition, the residual solvents such as N, N‐dimethylformamide (DMF), and N‐Methyl pyrrolidone (NMP) continue to decompose under high potential due to the relatively high highest occupied molecular orbital (HOMO) energy, which will cause the rapid capacity decay of high‐voltage cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…Second, when matching with the Li metal anode, the alkaline radicals on the surface of Li metal rapidly induce the uncontrolled dehydrofluorination of PVDF‐HFP (–(CH 2 –CF 2 )‐ + LiOH → –(CHCF)‐ + LiF + H 2 O), resulting in the formation of unstable solid electrolyte interphase (SEI) with porous structure. [ 33,34 ] The porous structure of the SEI layer leads to continuous side reactions between Li metal and solvated molecules, resulting in the further deterioration of interfacial stability. In addition, the residual solvents such as N, N‐dimethylformamide (DMF), and N‐Methyl pyrrolidone (NMP) continue to decompose under high potential due to the relatively high highest occupied molecular orbital (HOMO) energy, which will cause the rapid capacity decay of high‐voltage cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further investigate these possibilities, XPS analysis of pristine PVDF and PVDF obtained after treatment with the catalyst complex in NMP, under similar experimental condition during graft copolymerization (excepting the monomers), was carried out and presented in Figure S2. The absence of the C­(1s) signal at binding energy ∼284.6 eV (corresponding to C  C ) in treated PVDF as well as in PVBDF indicated no dehydrofluorination occurred under the present polymerization conditions. Interestingly, new signals observed at 197.6 eV (for Cl, 2p 3/2 ) and 199.5 eV (for Cl, 2p 1/2 ) and reconvolution of the C­(1s) producing signal at 288.3 eV of treated PVDF were possibly due to the transitions of C­(1s) of the (> C FCl) units .…”
Section: Resultsmentioning
confidence: 79%
“…35 In order to further investigate these possibilities, XPS analysis of pristine PVDF and PVDF obtained after treatment with the catalyst complex in NMP, under similar experimental condition during graft copolymerization (excepting the monomers), was carried out and presented in Figure S2. The absence of the C(1s) signal at binding energy ∼284.6 eV (corresponding to C�C) 36 units. 37 Thus, it might be argued at this stage that the PVDF backbone upon treatment with the present catalyst complex results in formation of some (>CClF) units due to halide exchange 35 A possible explanation behind the appreciable degree of control observed during grafting may be the faster deactivation of the propagating radicals by the relatively less-halidophilic 7 cupric chloride-based complex present as contamination with the CuCl-based catalyst complex (the stock CuCl has been found to contain 4.62% of CuCl 2 , as presented in the Supporting Information S4).…”
Section: Synthesis Of Pvdf-grafted Di-/tercopolymersmentioning
confidence: 99%
“…The polar phases of PVDF can be produced by applying external field, such as high pressure, [5][6][7] mechanical stretching, [8][9] and high-voltage electrostatic field [10][11][12] or by the intermolecular interaction between the additives and PVDF, [13] among which adding additives proves to be the most convenient and effective preparation method. It has been reported that the addition of inorganic additives such as nanoclay, [14,15] BaTiO 3, [16,17] potassium bromide (KBr), [18] molybdenum disulfide (MoS 2 ), [19,20] zinc oxide (ZnO), [21,22] graphene, [23][24][25] and carbon nanotube [26][27][28][29] can boost the electroactive phases of PVDF mainly through the electrostatic interaction between the charged surface and the CH 2 or CF 2 dipoles of PVDF.…”
Section: Doi: 101002/macp202100416mentioning
confidence: 99%